Experts' Results in Blunt Thoracic Aortic Injury are Reproducible in Lower Volume Tertiary Institutions. Early and Mid-term Results of an Observational Study. (November 2017) - Ghazy, Tamer; Mikulasch, Sandra; Reeps, Christian; Hoffmann, Ralf-Thorsten; Wijatkowska, Kasia; Diab, Abdel-Hannan; Kappert, Utz; Matschke, Klaus; Weiss, Norbert; Mahlmann, Adrian
Abstract : Objectives: The aim of this study was to evaluate the early and mid-term clinical results, the device performance, and the mid-term re-intervention rates of patients suffering blunt thoracic aortic injury (BTAI) managed by a multidisciplinary team in a low-volume BTAI centre. Methods: This was a retrospective observational study in a tertiary hospital setting. From December 2005 to March 2016, all patients over 18 years old admitted with BTAI were included in the study. No exclusion criteria were applied. The study data were collected and analysed retrospectively. Follow-up of survivors included computed tomography imaging 3 and 9 months post-procedure, then annually. Results: Twenty-eight patients were included in the study. Their mean age was 42 ± 16 years and 89% were male. A contained aortic rupture was diagnosed in 20 patients, a Stanford type B dissection in six, and intramural haematoma in two patients. Multidisciplinary evaluations were performed and an intervention was indicated in 25 patients (89%), four of whom died before the intervention. Nineteen patients underwent thoracic endovascular aortic repair of the descending thoracic aorta and two patients underwent a frozen elephant trunk procedure. The procedures were performed 0.7 ± 1.2 days after injury. All procedures were successful. There were no device related complications. The post-operative 30 day mortality was 5%, with one patient dying on the day of operation from other vascular injuries. The 30 day mortality of all patients was 18%. The median mid-term follow-up period was 786 days. All 30 day survivors survived the follow-up period. The mid-term imaging showed stable results in 19 patients. Two patients required frozen elephant trunk procedures after 240 and 681 days and both procedures were successful. Conclusions: In a low volume centre, a multidisciplinary team using a standardised protocol with the endovascular first approach demonstrated excellent outcomes, similar to those of large centres. If the aortic trauma is adequately managed, the patient's outcome is closely related to the additional trauma. Graphical abstract: